Kualitas Melengkapi Teks Rumpang sebagai Strategi Memahami Informasi secara Kritis - Zulhafizh Zulhafizh; Silvia Permatasari; Elvrin Septyanti; Tria Putri Mustika; Oki Rasdana (Universitas Indraprasta PGRI Jakarta, 2023)
This study aims to analyse the quality or ability to complete gap text as a strategy for understanding information. The research method uses a descriptive-inferential quantitative approach. The research sample was 28 students of the Indonesian Language and Literature Education Study Program, FKIP, Riau University, which was carried out in 2022. The data collection technique was a test on gap text. Data analysis techniques included scoring and assessing the results of respondents' entries through descriptive statistics and decision analysis through normality tests and one-sample t tests. The results of the analysis of completing incomplete text as a strategy for understanding information were an average of 71,50 with the independent category. The normality test had a normal distribution through the Shapiro-Wilk value of 0,949 at a significance of 0,187, the t test obtained ttable -1,704 < tcount 0,125 < ttable +1,704 and a significance value of 0,902 > 0,05. The test results provide a conclusion that the quality of completing incomplete text can help in understanding the information in a text. Significantly, the quality of completing incomplete text had a positive impact on strategies for understanding information in the text.